A Radiation Levels Measurement at Workplace of Cyclotron-PET/CT Facilities (in Karachi) using TLD Dosimeters - Kauser Perveen; Ayesha Mohsin; Hira Nadeem; Syed Mishkat Ali; Khalid Hussain (Sir Syed University Research Journal of Engineering and Technology, 2023)
Cyclotron is the most widely used proton particle accelerator for production of short lived radionuclides particularly F-18 for diagnostic purpose in oncology imaging. Currently, only Fluorine [F-18] is being produced in Pakistan. F-18 is tagged with glucose analogue and converted into [18F] FDG (Fluorodeoxyglucose) by synthesis process. [18F] FDG emits positron and, via annihilation process, produces two gamma photons of 511keV energy, which is of great concern for occupational safety. Therefore, a study was carried out to assess the dose incurred by radiation workers working in controlled and supervised areas of cyclotron facility.